Penerapan Model Pembelajaran Problem Based Learning (PBL) Dipadu Metode Pembelajaran Snowbal Throwing dalam Meningkatkan Hasil Belajar IPA Kelas VIII SMP YP-PGRI 4 Makassar - Astuti, Wiwik Wiji; Nurveryani, Andi (Universitas Negeri Makassar, 2021)
Abstract. This research is a classroom action research (Classroom Action Research) which aims to determine the improvement of studentsâ€ biology learning outcomes through the Problem Basied Learning (PBL) Learning Model combined with the Snowball Throwing Learning Method. The subjects of this study were 25 students of class VIII SMP YP-PGRI 4 Makassar. Data collection techniques were carried out using learning activity data obtained through observation sheets and learning outcomes data obtained through biology learning outcomes test which were then analyzed using quantitative and qualitative descriptive statistical analysis techniques. Based on the results of data analysis that has been carried out, it can be seen that there is an increase in biology learning outcomes for students of class VIII SMP YP-PGRI 4 Makassar who are taught through the Problem Based Learning (PBL) Learning Model combined with the Snowball Throwing Learning Method which can be seen from the average value of the results, leraning in the first cycle that is 68,8 to 82,8 in the second cycle.Keywords: problem based learning, snowball throwing, learning outcomes